About The Hierarchy Of Text - Mustafayeva, Gunel Tofiq (Advances in Social Sciences Research Journal, 2017)
The article deals with the hierarchy of texts. It states that a text is formed by means of language signs, and it has verbal, visual, audial and other signs which are connected to one another due to the ordering of signees. All the signs have the character of communication. The importance of semiotic means has already been proved. The sign character of texts can be considered as materials, on the other hand can also be introduced having the character of non-material. That is why the text is introduced as “denotant-demonstrant-significant” triangles. Text can be understood carrying the completeness of expressiveness and contents. In this case the content side of the texts deal with the information, and the formal side of it deal with structures that form the texts. Texts cannot be formed outside these two factors. The hierarchy of texts is also used to state the inside and outside factors of the texts. All the state facts have widely been analyzed in the texts.